Physical and mechanical properties enhancement of beaten oil palm trunk pulp and paper by optimizing starch addition: Towards sustainable packaging solutions - Low, L.Q.; R.A., Ilyas; Jalil, R.; Husain, S.N.Hawanis; Ibrahim, R.; A.A., Azriena H.; Zuhri, M.Y.M.; M.A., Ainun Z.; ., W. Fatriasari; N., Hastuti; ., D. Amelia (Elsevier, 2024)
Paper is a commonly utilized material in various aspects of daily life. However, the pulp and paper industry face environmental challenges related to pollution and deforestation. The utilization of non-wood fibres, such as agricultural waste of oil palm (Elaeis guineensis Jacq.) from oil palm trunk (OPT), may offer sustainable alternatives to wood-based pulp. However, the mechanical properties of OPT paper in this study need improvement to compete with wood-based paper. Incorporating starch as an additive can enhance the mechanical and physical properties of OPT paper. This study aimed to develop and characterize the unbleached OPT paper prepared via kraft and soda pulping methods and beating treatment. The mechanical properties are enhanced by adding starch at 5,10,15, and 20 %. Findings exhibited that the addition of starch increased the tensile strength of OPT papers but decreased tear resistance. Hence, the papers have a high potential to be applied as non-woody pulp source-sustainable alternative raw materials for packaging. © 2024 Elsevier B.V.